Strategic Intervention Material (SIM)-based Instruction in Teaching Global Warming Concepts in 9th Grade Science - Jill R. Gabucan; Joje Mar Perino Sanchez (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2021)
A quasi-experimental research with pretest-posttest design was conducted to investigate the effectiveness of the Strategic Instructional Material (SIM)-based teaching in improving the Science performance in Global Warming of the ninth grade students of a mountain school in Cebu City, Philippines. Two experimental groups consisting of 15 students each were exposed to the use of modules and SIM-based teaching respectively. Study findings revealed that both groups had Below Average performances in the pretest, and the former group had Average performance while the latter group had Above Average performance in the posttest. Moreover, both groups manifested significant mean improvement from the pretest to posttest, signifying the essential use of modules and SIM in the teaching-learning process. Experimental group 2 acquired higher mean gain than experimental group 1 and had a Very High perception towards the use of SIM in the teaching of Global Warming in Science. The study concluded that SIM-based teaching is a more effective scaffold in improving students’ performance in the concepts of Global Warming. Furthermore, the researchers recommend the use of SIM for remediation and regular classes, and encourage administrators, Science supervisors and teachers construct SIMs not only on least mastered skills but also on all skills covered by the lesson.